An Innovative Method for Using Himalayan Alkaline Water to Enhance the Production of Bioactive Secondary Metabolites in Aloe Vera Barbadensis - Saeed, Junaid H.; Muttaleb, Hayder S. (American Journal of Biology and Natural Sciences, 2025)
This work utilized Himalayan alkaline water technology, in specific proportions, to enhance the active substances in the Aloe Vera Barbadensis plant. This approach aims to leverage the plant’s known medicinal and economic benefits, stemming from its therapeutic compounds utilized since antiquity in medicine and cosmetics. By applying Himalayan alkaline energy water to the aloe vera plant, an increase in these active substances was achieved through a simple, scientific method. The Himalayan alkaline water has secured international and local patents, signifying a breakthrough due to its unique properties that improve active substance effectiveness per unit area compared to regular water. Salicylic acid, a key compound with unique properties found in aloe vera, was a particular focus. Active substances were measured using specific devices, comparing plants watered with regular water versus Himalayan water (both neutral and alkaline) through lyophilization and pH analysis. Gas chromatography–mass spectrometry (GC–MS) was employed to detect substances like flavonoids. Results indicated that alkaline Himalayan water surpassed both neutral Himalayan water and regular water in terms of the proportion and quantity of active ingredients.